Antioxidant Properties of the Leaves of Chromolaena odorata Linn - Bhargava, D; Mondal, CK; Shivapuri, JN; Mondal, S; Kar, S (Journal of Institute of Medicine Nepal, 2013)
Introduction: Chromolaena odorata Linn (Asteraceae) locally known as “Banmara” has the reputation of being used as a medicinal herb in Nepal. A systemic search for drug research in now considered to be a rational approach. Therefore in the present study an effort has been made to evaluate the antioxidant activity of the leaves of the above mentioned plant. Methods: In the present research work the ethanolic and methanolic extract of leaves of the plant C. odorata Linn was assessed for free radical scavenging and antioxidant activity. In this work the ability of the extract to scavenge nitric oxide, hydroxyl radical and 1,1-diphenyl-2- picrylhydrazyl (DPPH) were used to assess its free radical scavenging potentials. Results: The DPPH radical inhibition (%) was 59.10, 52.13 and 81.12 for ethanolic extract, methanolic extract and ascorbic acid respectively. Similarly ethanolic and methanolic extract also showed significant free radical scavenging action against nitric oxide and hydroxyl radical. Conclusion: Against the backdrop of many known medicinal properties of this plant its ethanolic and methanolic extract of leaves reveals significant antioxidant properties. DOI: http://dx.doi.org/10.2126/joim.v35i1.8900 Journal of Institute of Medicine, April, 2013; 35:53-57